(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This article shows how to apply digital technology as an innovative solution in enterprise financial management and their role and advantages in changing enterprise management. Digital technology plays an important role in ensuring that financial management is efficient and light. The article will analyze how these solutions help to better review the processes of enterprise financial management.